ARISING ISSUES AMONG WOMEN FISHERMAN REGARDING THE PRODUCTION WORKSHOP AID - Suria Fadhillah Md Pauzi; Shamsinar Rahman; Zuriani Yaacob; Ramlan Mustapha; Mohd Azim Zainal; Mohamad Sahizam Musa (Journal of Islamic, Social, Economics and Development, 2024)
The Women's Fisherman Group (KUNITA) Programme was officially inaugurated in 1983 under the supervision of The Fisheries Development Authority of Malaysia (LKIM). Women have a high potential of generating supplement income for their families, and LKIM has assisted them by providing manufacturing workshops. The purpose of this paper is to explore the concerns that have arisen among members of the Women Fisherman Group (KUNITA) regarding production workshop aid from The Fisheries Development Authority of Malaysia (LKIM). The qualitative method was adopted in discussing the issue. In-depth interviews were conducted with twenty-seven people. This study discovered three emerging challenges related to LKIM decision making, workshop aid application, and workshop maintenance. This study also recommends two solutions i.e. to strengthen the practise of backyard workshop and to provide the KUNITA workshop permanent property status.